Epistemological Integration in the Islamic Golden Age: Reassessing Muslim Contributions to Global Science - Syarif Bahaudin Mudore; Moh Restu Hoeruman; Muhammad Shaleh Assingkily; Andi Nurindah Sari; Rahman Subha; Mustapa Ahmad (Journal of Islamic Civilization and Culture Review, 2026)
This study examines the epistemological model of knowledge integration developed by Muslim scholars during the Islamic Golden Age and its contribution to global scientific development. Previous studies on Islamic science have largely focused on descriptive-historical narratives and have not sufficiently explored the integration of revelation, rationality, and empirical inquiry within Islamic scientific traditions. In addition, many historiographical accounts continue to portray Muslim scholars primarily as transmitters of Greek knowledge within a Eurocentric framework. This study employs a qualitative library research approach using intellectual history as its analytical framework. Data were collected from classical Muslim scientific works, historical manuscripts, and contemporary historiographical studies and analyzed through thematic content analysis and critical historiographical interpretation. The findings reveal that scientific development in the Islamic world involved not only the preservation of earlier intellectual traditions but also epistemological reconstruction and methodological innovation. Muslim scholars developed a holistic scientific paradigm integrating revelation, rational reasoning, and empirical observation, contributing significantly to advancements in mathematics, medicine, astronomy, optics, and philosophy. Furthermore, the transmission of Islamic scientific traditions to Europe occurred through complex processes involving translation movements, educational institutions, intercultural exchanges, and intellectual mobility across civilizations.